2019
DOI: 10.1007/s12520-019-00824-5
|View full text |Cite
|
Sign up to set email alerts
|

The application of 3D modeling and spatial analysis in the study of groundstones used in wild plants processing

Abstract: In recent years, several works have proved the reliability of the application of 3D modeling and spatial analysis in the study of stone tool use. Monitoring surface morphometry resulting from the use of lithic tools has the potential to objectively quantify and identify patterns of modifications associated to specific activities and worked materials. In particular, the combination of surface morphometry with a systematic experimental framework and use wear analysis has the potential of foreseeing residue distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 49 publications
3
23
0
1
Order By: Relevance
“…This analysis confirmed that the study area was economically utilized almost during the whole studied period. The advantages of analyzing the historical, topographic maps and orthophotos for the research of archaeological findings were also pointed out in the works of Zupancich et al [44], Gennaro et al [45], Tache et al [46], Drap et al [47] and so on.…”
Section: Discussionmentioning
confidence: 95%
“…This analysis confirmed that the study area was economically utilized almost during the whole studied period. The advantages of analyzing the historical, topographic maps and orthophotos for the research of archaeological findings were also pointed out in the works of Zupancich et al [44], Gennaro et al [45], Tache et al [46], Drap et al [47] and so on.…”
Section: Discussionmentioning
confidence: 95%
“…We also investigated the role of residue adhering to the used surfaces and its impact on surface measurements and appearance. Our results indicate that, while the application of synergetic approaches is still rare 11,12,14,19,20,23,30 , the combination of qualitative and quantitative analyses is likely to provide accurate and reliable functional interpretations where the researcher's subjectivity has an active role. We also offer a preliminary quantitative functional dataset associated with the use of sandstone GSTs and discuss the interpretative potential of specific variables for assessing different materials.…”
Section: Functional Analysis Of Sandstone Ground Stone Tools: Argumenmentioning
confidence: 86%
“…3D models of the experimental replicas were created through Close Range Photogrammetry 38 . Using the same acquisition standards applied by Zupancich et al 12 To analyze the topography of each tool in its entirety, a 360° surface analysis was performed following the methodology proposed by Benito-Calvo et al 11 . At first, a convex hull was created in Meshlab (v.2020.03) for each tool.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large variety of qualitative and quantitative techniques, including use wear analysis, mechanical tests, 3D modelling, surface morphometrics, spatial and residue analyses and experimental frameworks have been proposed (Arroyo and de la Torre 2020;Benito-Calvo et al 2015Caricola et al 2018;Caruana et al 2014;Delgado-Raack et al 2009;Hayes et al 2017;Hayes and Rots 2019;Procopiou et al 2002;Zupancich et al 2019). However, scholars have debated the lack of a shared analytical protocol for functional analysis (Cnuts and Rots 2018;Hayes et al 2017;Marreiros et al 2020;Zupancich et al 2019). In particular, arguments have been raised concerning the application of qualitative and quantitative approaches, the protocols for extracting ancient residues and the risk of modern contamination.…”
Section: Introductionmentioning
confidence: 99%